Perspektif Pemilik Audio Sound System terhadap Penolakan Masyarakat Sidoarjo atas Operasional Sound Horeg - Nafisa Rifdatul Maghfira; Arief Sudrajat (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The phenomenon of sound horeg as a form of modern entertainment has grown rapidly in Sidoarjo Regency and is commonly used in community events such as celebrations and carnivals. However, its operation often faces public rejection due to noise disturbance, environmental discomfort, and social conflict. On the other hand, for audio sound system owners, sound horeg serves as a source of income, a medium for creative expression, and a form of social identity. This study aims to examine the perspectives of audio sound system owners toward community rejection of sound horeg operations and to analyze the adaptive strategies they employ in response to such rejection. This research uses a qualitative descriptive method and is analyzed through George Herbert Mead’s symbolic interactionism theory. Data were collected through observation, in-depth interviews, and documentation involving audio sound system owners operating in Sidoarjo Regency. The findings show that audio sound system owners perceive sound horeg not merely as entertainment, but also as a symbol of business existence and economic opportunity. Community rejection is understood as the result of differing perspectives and interests between business actors and local residents. To address this rejection, sound system owners implement adaptive strategies such as adjusting sound volume, limiting operational hours, and engaging in communication and negotiation with the surrounding community. This study highlights that conflicts related to sound horeg are social issues involving interaction, communication, and the negotiation of meanings within public spaces.